GIS-material for the archaeological project: A flat-grave cemetery in Agetomta - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to house construction on the property Agetomta 2:3, Styrstad parish, Norrköping city, a preliminary investigation was performed during autumn 2005. A flat-grave cemetery from the Early Roman Iron Age was discovered. Several graves containing soot and charcoal as well as burnt bones, pottery and remains of resin seal were found. A final excavation is thus suggested to be performed before any development of the area is started.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the preliminary investigation was to determine the extent, type and dating of the archaeological sites RAÄ 6, 7 and 133.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Med anledningen av en husbyggnation inom fastigheten Agetomta 2:3, Styrstads socken, Norrköpings kommun, utfördes en arkeologisk undersökning under hösten 2005. Vid denna påträffades ett flatmarksgravfält från äldre romersk järnålder. Ett flertal brandgravar vilka innehöll sot, kol och brända ben liksom keramik och resterna efter hartstätning framkom. Arkeologisk slutundersökning bör därför ske innan eventuell exploatering av området.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att bedöma utbredning, art och ålder av fornlämningsområdet tillhörande RAÄ 6, 7 och 133.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Ett flatmarksgravfält i Agetomta
Keywords: Roman Iron Age; romersk järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi